CHARACTER EDUCATION FOR MENTAL RESILIENCE: A SYSTEMATIC LITERATURE REVIEW ON CHILDREN'S WELL-BEING IN THE AI ERA - Fatrizal; Evi Fussalam, Yahfenel (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study analyzes the relationship between character education and children's mental resilience in the era of artificial intelligence, focusing on protective factors and developing an integrative conceptual model. Using a Systematic Literature Review (SLR) approach with the PRISMA protocol, 144 articles from Scopus-indexed journals published between 2020 and 2025 were screened, and 15 relevant studies met the inclusion criteria. The study results indicate that character education plays a strategic role in strengthening children's resilience through the values of self-regulation, empathy, responsibility, solidarity, and the search for meaning in life. Identified protective factors include positive parent-child bonds, peer support, family resilience, and community involvement, while risk factors include device dependence, family conflict, poverty, and parental stress. The proposed conceptual model emphasizes a holistic, differentiated, and multilevel approach with simultaneous involvement of schools, families, and communities. The findings of the majority of studies confirm that character education not only shapes morality but also functions as an ecosystem strategy to strengthen children's mental resilience in facing digital and social challenges in the era of artificial intelligence. This study recommends the development of a multidimensional resilience theoretical framework, its integration into the curriculum